O ensino por investigação em laboratório aberto como proposta didática no ensino de eletrodinâmica - Silva, Alexandre Abraão Muriana da (2017)
This work reports a set of activities developed under didactic proposal based on teaching by inquiry in an open laboratory with a group of high school students from a State School of Paraná, Brazil. In these activities the students evaluated, through a sequence of questions, basic concepts about electricity through the construction of circuits with lamps as resistors and other materials of easy access. The approach used is analternative to the traditional approach based on the use of chalk board and chalk. Aims to verify the contributions of a didactic proposal based on research teaching for the conceptual evolution on electricity in high school students. The research under taken was of a qualitative approach of applied nature with exploratory objectives and, as far as the procedural basis, it was figured as an action research. The data collection instruments were pieces that presented questions to be answered in consonance with the stages of teaching by research in open laboratory recommended in the literature. The observation of there action of the students to the situations to which they were exposed demonstrated that the proposal is motivating, because the students carry out the activities with enthusiasm and curiosity. It also demonstrated that previous ideas were built, reaching a deeper degree of elaboration than their previous conceptions. The evidence of learning, such as the level of elaboration of concepts and the use of specific terms in written argumentative interactions, evidences that the proposal was effective for the conceptual evolution on electrodynamics for the screen group.